The Impact of Enhancing Phone Activeness on the Negative Effect Induced by the Presence of a Cell Phone - Liu, Wenjuan; Dempo, Akihiko; Shinohara, Kazumitsu (Frontiers in Psychology, 2022)
In the information-driven workplace, cell phones have gradually become irreplaceable. Although the use of work-related cell phones can bring convenience, recent research has demonstrated that the presence of a cell phone can impair cognitive task performance by reducing available attentional resources and suggested that the effect of the phone’s presence can be influenced by phone-related factors. The current study focused on the relationship between this effect and phone activeness and conducted two experiments to investigate whether increasing phone activeness is associated with a stronger effect from the phone’s presence by using a dual task paradigm (primary: 0-back task, secondary: luminance-change detection task). Phone activeness was manipulated by two potential factors: the phone’s power state (control, powered-off, powered-on) and physical contact state (the phone was placed on the desk or held in the hand). The results showed that secondary task performance decreased with the phone’s presence, regardless of its power state and contact state. This indicated that the presence of the phone only affects the available attentional resources devoted to the peripheral visual field where the secondary task stimuli occurred; however, the effect of the phone’s presence was not moderated by phone activeness. The current findings provided several extended understandings related to the negative effects caused by the presence of the cell phone and their underlying mechanisms.